Estimasi dan Peramalan Jumlah Penduduk Miskin Menggunakan Model Tren Non-Linear Kuadratik di Sulawesi Selatan - Hidayat, Rahmat; Ashari, Nur Wahidin (Pusat Studi Bahasa dan Publikasi Ilmiah, 2025)
Poverty is a complex and multidimensional issue, interconnected with various aspects, including social, economic, cultural, and other aspects. The number of poor people in Indonesia was 25.14 million in March 2019. In South Sulawesi Province in March 2019, there were approximately 767,800 poor people. As a preventive measure against increasing poverty rates, it is necessary to forecast the number of poor people so that the government can plan policies. The data used in this study is data from 2008-2019 sourced from the Central Statistics Agency of South Sulawesi Province. This study uses Non-Linear Trend Analysis, specifically the Quadratic Method, to forecast the number of poor people. This method is suitable for data spanning 10 or more periods. The Quadratic Method has an R-Square value of 86.48% and a MAPE of 2.69%. The results of the forecast for 6 years show that the number of poor people in South Sulawesi Province has increased.